High rate of false positive malaria rapid diagnostic tests in a district hospital in Uganda - Mortazavi, Susanne E.; Lugaajju, Allan; Ivarsson, Anna-Clara; Karlsson Söbirk, Sara; Norrgren, Hans; Persson, Kristina E. M. (Frontiers in Malaria, 2025)
BackgroundMalaria remains a significant health burden, particularly in Uganda, which has one of the highest incidence rates globally. Rapid diagnostic tests (RDTs) are widely used for malaria diagnosis due to their ease of use and affordability in resource-limited settings. However, false-positive RDT results may lead to unnecessary antimalarial treatments and missed diagnoses of other febrile conditions. This study aimed to evaluate the diagnostic accuracy of RDT compared to microscopy and loop-mediated isothermal amplification (LAMP) in a malaria-endemic region of Uganda.MethodsA prospective study was conducted with 225 febrile individuals diagnosed with malaria using RightSign Malaria Ag HRPII/Pan Plasmodium Aldolase RDT (Hangzhou Biotest Biotech Co., Ltd., China) at Iganga General Hospital, Uganda. Blood samples were analyzed using microscopy and LAMP. Demographic information, malaria history, and parasitemia levels were also recorded.ResultsAmong the RDT-positive participants, 48% tested negative by microscopy, and 45% of these were also negative by LAMP, indicating that 20% of all RDT-positive individuals were likely false positives. Overall, 66% (149/225) of RDT-positive cases were confirmed as true positives.ConclusionsThis study identified a high rate of false positives with the tested RDT, risking inappropriate treatment and missed diagnoses of other illnesses. It is essential that healthcare facilities use RDTs validated and recommended by the World Health Organization (WHO) to ensure high specificity and accuracy, particularly in resource-limited settings where alternative diagnostic methods may not be available.